Quantum dynamics of scalar particles in the space–time of a cosmic string in the context of gravity’s rainbow - Santos, L.C.N.; Mota, C.E.; Barros, C.C.; Castro, L.B.; Bezerra, V.B. (Annals of physics, 2020)
We analyze the dynamics of scalar particles in gravity’s rainbow considering the space–time of a cosmic string in this modified gravity. Thus, we solve the Klein–Gordon equation for two types of potential in which two possible rainbow functions are selected. In all cases studied we obtain exact solutions for the wave equation, derive the energy spectrum, analyze it in detail and discuss the dependence of the results with the choice of the rainbow functions.